Cybersecurity Public Sector Threats and Responses - Andreasson, Kim J. (Taylor & Francis, 2011)
The Internet has given rise to new opportunities for the public sector to improve efficiency and better serve constituents in the form of e-government. But with a rapidly growing user base globally and an increasing reliance on the Internet, digital tools are also exposing the public sector to new risks. An accessible primer, Cybersecurity: Public Sector Threats and Responses focuses on the convergence of globalization, connectivity, and the migration of public sector functions online. It identifies the challenges you need to be aware of and examines emerging trends and strategies from around the world. Offering practical guidance for addressing contemporary risks, the book is organized into three sections: Global Trends-considers international e-government trends, includes case studies of common cyber threats and presents efforts of the premier global institution in the field National and Local Policy Approaches-examines the current policy environment in the United States and Europe and illustrates challenges at all levels of government Practical Considerations-explains how to prepare for cyber attacks, including an overview of relevant U.S. Federal cyber incident response policies, an organizational framework for assessing risk, and emerging trends Also suitable for classroom use, this book will help you understand the threats facing your organization and the issues to consider when thinking about cybersecurity from a policy perspective.